2’-Fucosyllactose modulates the function of intestinal microbiota to reduce intestinal permeability in mice colonized by feces from healthy infants - Qingxue Chen; Liu Yang; Fangqin Xiang; Ignatius Man-Yau Szeto; Yalu Yan; Biao Liu; Jinju Cheng; Lu Liu; Bailiang Li; Sufang Duan (Food Science and Human Wellness)
2’-Fucosyllactose (2’-FL) shows the potential to support intestinal health as a natural prebiotic that bridges the gap between infant formula feeding and breastfeeding. However, the effect and mechanism of 2’-FL in improving intestinal permeability are not clear. In this study, we constructed human microbiota-associated (HMA) mouse models by colonizing healthy infant feces in mice with antibiotic-depleted intestinal microbiota. The protective effect of 2’-FL on the intestinal permeability was explored using the HMA mouse models, and the combination of metagenomics was used to analyze the possible mechanisms by which the microorganisms reduced the intestinal permeability. The results showed that 2’-FL decreased the concentration of markers of intestinal permeability (enterotoxin and diamine oxidase (DAO)) and increased the expression levels of tight junctions (occludin and claudin). Metagenomics revealed the enrichment of Bifidobacterium and increased the expression of glycoside hydrolases (GHs), including GH31, GH28, and GH5. In conclusion, 2’-FL strengthened intestinal permeability function by improving microbiota composition to control the translocation of harmful substance.